Human-Robot Personal Relationships Third International Conference, HRPR 2010, Leiden, The Netherlands, June 23-24, 2010, Revised Selected Papers - Lamers, Maarten H.; Verbeek, Fons J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Human-Robot Personal Relationships, held in Leiden, The Netherlands, in June 2010. The 16 revised full papers presented together with 2 invited papers and 1 keynote lecture were carefully reviewed and selected from 22 submissions. The papers feature and discuss studies of personal relationships with artificial partners, their formation, their possibilities and their consequences. Such personal relationships are increasingly attracting attention from scientific fields as (social) robotics, human-computer interaction, artificial intelligence, psychology, philosophy, sociology.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Computation by Abstract Devices; Software Engineering